COST AND TIME ANALYSIS USING THE CRASHING METHOD ON THE PROBOLINGGO – BANYUWANGI TOLL ROAD PROJECT PEKET 2: STA 9+000 – 20+200 - Nugraha, Budidarma Ardi; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2023)
The government is building toll roads in various regions in Indonesia to realize economic acceleration and minimize economic inequality in society. However, based on facts on the ground, there are still many delays in toll road construction projects which are detrimental so it is necessary to take steps to accelerate the work. The aim of this research is to analyze the time and costs of accelerating the Probolinggo – Banyuwangi Toll Road construction project STA 9+000 – 20+200 using the Crashing Method. This type of research is quantitative research with the research subject being PT. Hutama Karya Indonesia (HKI) as the project implementing contractor. The research uses secondary data, namely the Draft Expenditure Budget (RAB), Schedule, weekly reports, and project costs for the completion of Toll Road construction work. The data collection method was carried out using observation and documentation methods. The research data analysis technique uses the Crashing. The results of research state: 1) On work on the Probolinggo – Banyuwangi Toll Road project Job STA 9+000 – 20 +200 job time can be accelerated to 311 days, which originally lasted 394 days. 2) Application of the Crashing Method to the Probolinggo Toll Road project– Banyuwangi STA Jobs 9+000 – 20+200 with critical path on public works, workplace cleaning, earthworks, drainage, sub grade, aggregate base layer, pavement, work others, traffic light lighting and electrical works, plazas Tolls, and work on toll facilities and toll gate offices can saving 115 days of work time with additions cost Rp. 72,941,450,191.64.